Peluang dan Tantangan Bisnis Televisi Lokal Paska Regulasi Televisi Berjaringan - Wahyu Sudarmawan (Program Studi Ilmu Komunikasi, 2007)
The Act Number 32 about Broadcast had been established at 28 December 2002, but in fact, there are always any obstacles that impede the realization, particularly the vague regulation and policy. One of them is the policy about networking TV in Indonesia. Although by 29 December 2007, there are indeed few TV stations that have been performed the network broadcasting, for example RCTI, SCTV, and ANTV, but this policy can't be implemented easily. On the other hand, this policy threatens the existing of local TV station. This article aimed to draw the real challenge that a TV local must face towards the network broadcasting policy. Besides, this article will also explain the potential of local TV in order to compete with the networking TV, and recommend some good ways to manage a local TV so it could be more accepted and trusted both by the audiences and the advertisers.